Sensitivity Analysis of Multiple Eigenvalues (Ⅰ) (Journal of Computational Mathematics, 2018)
The technique described in [9] is used to discuss the sensitivity of multiple eigenvalues and corresponding eigenspaces of symmetric eigenproblems analytically dependent to several parameters. The results may be useful for investigating problems of stability and response analysis of linear structures.